2020
DOI: 10.1039/d0ay01558j
|View full text |Cite
|
Sign up to set email alerts
|

Research on the distribution of neonicotinoid and fipronil pollution in the Yangtze River by high-performance liquid chromatography

Abstract: Neonicotinoid and fipronil insecticides have been consumed worldwide, particularly in China. There is a growing interest in the environmental research community about the occurrence, fates, sources, and risks of neonicotinoids...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…The mean (range) concentration of ∑NEOs in PRE was 33.9 (19.6−104) ng/L. The DFs and concentrations of NEOs found in PRE by this study were much higher than those observed in the Yangtze River Estuary (range = ND−12.45 ng/ L, mean = 3.50 ng/L) 34 and the mouth of Jiaozhou Bay (range = ND−0.38 ng/L, mean = 0.17 ng/L) in China. 35 Previous studies have reported that regional differences in pesticide use in China increase from north to south China.…”
Section: ■ Results and Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The mean (range) concentration of ∑NEOs in PRE was 33.9 (19.6−104) ng/L. The DFs and concentrations of NEOs found in PRE by this study were much higher than those observed in the Yangtze River Estuary (range = ND−12.45 ng/ L, mean = 3.50 ng/L) 34 and the mouth of Jiaozhou Bay (range = ND−0.38 ng/L, mean = 0.17 ng/L) in China. 35 Previous studies have reported that regional differences in pesticide use in China increase from north to south China.…”
Section: ■ Results and Discussioncontrasting
confidence: 59%
“…Currently, there is a scarcity of global studies that focus on investigating NEOs in seawater. 4,34,35,41 In this study, the concentrations of ∑NEOs found in SS_XS (range = 19.4− 72.8 ng/L, mean = 27.0 ng/L) and in SS_NW (45.2−96.2 ng/ L, mean = 49.9 ng/L) of the South China Sea were much higher than those in the Bohai Sea (range = 0.23−4.70 ng/L) and Jiaozhou Bay (≤LOD−11.19 ng/L) of northeast China. 4,35 Similarly, it was observed that the concentration of ∑NEOs in this study exceeded those sites measured at the East China Sea (ND−0.38 ng/L).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The previous methods were mainly based on SPE and the sorbent generally had two sources, including commercial SPE cartridges and new SPE sorbent synthesized in the laboratory. Compared with the commercial SPE cartridges like C18 [18,19,24] and SDB-RPS [6], our self-made meltblown SPE cartridge could be reused and the core sorbent was taken from the medical mask, which was cheap and easy to obtain. Compared with the newly synthesized SPE sorbent, the preparation of meltblown SPE cartridge did not involve any chemical synthesis process, which fully met the needs of green analytical chemistry.…”
Section: Comparison With the Previous Methodsmentioning
confidence: 99%
“…[2,3]. In the past years, fipronil had been put into use in a large amount due to its high insecticidal activity and low toxicity to mammals [4][5][6][7]. However, some studies had shown that fipronil exhibited high toxicity and adverse effects on non-target beneficial insects such as butterflies, bees, dragonflies, and many aquatic organisms [4,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation